A D-Shaped SPR-Based PCF Sensor with an Extremely High-Amplitude Sensitivity for Measuring the Refractive Index - Wangyoyo Li; Yu Chen; Jianjie Xu; Menglin Jiang; Hui Zou (Micromachines, 2023)
In this work, a new D-shaped photonic crystal fibre sensor structure based on surface plasmon resonance (SPR) is purposed for measurement of analyte refractive index (RI). In this design, a silica cylinder is polished into a D-shaped silica material structure with a flattened surface where two Au nanowires are coated. Some air holes are omitted to form the core mode region. With the implementation of gold nanowires and a core region for the exciting SPR effect with variate physical values, analyte RI can be measured with a wavelength coverage from 850 to <semantics>1350<mspace width="3.33333pt"></mspace>nm</semantics>. The numerical simulation shows the maximum wavelength sensitivity of the purposed design achieves <semantics>19,600<mspace width="3.33333pt"></mspace>nm/RIU</semantics> with an RI coverage from 1.37 to 1.42. Moreover, the sensor has a tremendous amplitude sensitivity and the maximum absolute value is about <semantics>2300<mspace width="3.33333pt"></mspace>RIU−1</semantics>. Benefiting from these outstanding performance, the purposed structure can be given priority when it is applied in biomedical detecting and environmental assessment science.